2015
DOI: 10.1371/journal.pone.0137164
|View full text |Cite
|
Sign up to set email alerts
|

Folliculogenesis Is Not Fully Inhibited during GnRH Analogues Treatment in Mice Challenging Their Efficiency to Preserve the Ovarian Reserve during Chemotherapy in This Model

Abstract: As many chemotherapy regimens induce follicular depletion, fertility preservation became a major concern in young cancer patients. By maintaining follicles at the resting stage, gonadotropin-releasing hormone analogues (GnRHa) were proposed as an ovarian-protective option during chemotherapy. However, their efficacy and mechanisms of action remain to be elucidated. Mice were dosed with cyclophosphamide (Cy, 100–500mg/kg i.p) to quantify follicular depletion and evaluate apoptosis at different times. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…25, 26, 53, 54 Several groups reported that GnRH agonist-treated cancer patients resumed cyclic ovarian function, whereas patients in the chemotherapy alone group experienced amenorrhea. 55, 56 Ataya et al 21 showed that GnRH agonists administrated in parallel with cyclophosphamide significantly decreased the daily rate of follicular decline and the total number of primordial follicles lost during the chemotherapeutic insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25, 26, 53, 54 Several groups reported that GnRH agonist-treated cancer patients resumed cyclic ovarian function, whereas patients in the chemotherapy alone group experienced amenorrhea. 55, 56 Ataya et al 21 showed that GnRH agonists administrated in parallel with cyclophosphamide significantly decreased the daily rate of follicular decline and the total number of primordial follicles lost during the chemotherapeutic insult.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness and mechanisms of action of GnRHa, in protecting the ovarian reserve from chemotherapy-induced damage, is still debated. 24, 25, 26 …”
mentioning
confidence: 99%
“…In this study, LHRH‐a was mainly administered for ovarian protection Table . Previous reports showed ovarian protection by LHRH‐a, although not in a mouse model and was not effective on pregnancy.…”
Section: Discussionmentioning
confidence: 78%
“…Our results suggest that in mice, FSH-driven in vitro growth of small antral follicles is not adversely affected by GnRHa or antagonist co-treatment in vitro. It has been shown by different groups that mouse ovaries express the GnRH receptor (1)(2)(3)(4). In rats, the comparison of GnRH receptor expression at different follicular stages demonstrated that these mRNA levels of the GnRH-R gene vary depending on follicles degree of maturation as well as the estrous cycle stage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that although systemic administration of GnRH agonist (GnRHa) was efficient to disrupt estrus cycles, it failed to inhibit follicular development, irrespective of the doses and injection sites (subcutaneous or intramuscular). Around 20% of healthy growing follicles were still observed during GnRHa treatment, and serum FSH levels were not reduced either by antagonist or agonist treatment, suggesting that GnRHa does not suppress follicular growth even beyond the gonadotropin-dependent stage in mice (4). Also, it might be challenging to interpret the intra-ovarian actions of GnRH analogs when they are administered systemically due to its effect on the hypothalamic-pituitary-ovarian axis.…”
Section: Introductionmentioning
confidence: 99%